Comparative Linguistic Study On Relationship Of Aceh, Minangkabau And Gayo Languages - Raees Narhan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research focuses on the Austronesian or Polynesian Malay language family, which includes the languages of Acehnese, Minangkabau, and Gayo respectively. The fact that there are similarities in form and meaning, which are a reflection of the same historical legacy, is the basis for the hypothesis that the three languages are related to one another. This hypothesis is based on the fact that there are similarities. In this study, linguistic grouping methods and lexicostatistical approaches were utilized in order to investigate the kinship relationship that exists between the Acehnese language, the Minangkabau language, and the Gayo language. In the first level, Morris Swades selects 200 essential words for the fundamental vocabulary The referential method was used in order to provide this facts, and the technique that was utilized was the note-taking technique. The second step is to establish which duos of the three languages speak a cognate language. Third, compute the amount of time that has passed between each of the three languages. In the fourth step, you will calculate the error period in order to obtain a more accurate separation time. According to the findings, the Acehnese, Minangkabau, and Gayo languages were all classified as belonging to the same family of languages. It is estimated that 57 percent of Acehnese and Gayo speakers are related linguistically, whereas the percentages for Minangkabau and Gayo are 39 percent and 29.5 percent of Minangkabau Language  and Acehnese.